Style Influence Transformational Leadership and Organizational Culture on Employee Performance: JEL Classification: M12, M14, M54, J24, O15 - Hamid, Siti Hardiyanti Mustaina; Suyuthi, Nurmadhani Fitri; Samad, Abdul (Newinera Publisher, 2025)
This study aimed at investigating and discussing the effect of transformational leadership style on employee performance with the view of establishing whether organizational culture had an effect on employee performance and whether organization culture and transformational leadership style jointly had significant impact on employee performance at the Makassar Region V Airport Authority Office. The authors employed a quantitative approach in this study since the questionnaires were distributed to the employees in the Makassar Region V Airport Authority Office. The purposive method was used to select the research sample whereby 50 respondents would pass a questionnaire that was valid and reliable. Findings of this research point to the fact that: (1) transformational leadership style does not significantly and positively influence employee performance at Makassar Region V Airport Authority Office. (2) Organizational culture positively and significantly influences the performance of employees, and influences the performance of employees in part at the Makassar Region V Airport Authority Office. (3) At the same time, the organization culture and the style of leadership, transformational leadership style, significantly influence the employee performance at the Makassar Region V Airport Authority Office.